2015
DOI: 10.3892/or.2015.3912
|View full text |Cite
|
Sign up to set email alerts
|

Cellular leiomyoma with necrosis and mucinous degeneration presenting as pseudo-Meigs’ syndrome with elevated CA125

Abstract: Pseudo-Meigs' syndrome is a syndrome rarely caused by leiomyomas. Elevated CA125 usually suggests malignancy of the ovary. No reported case of pseudo-Meigs' syndrome presenting with necrosis and mucinous degeneration of uterine cellular leiomyomas (CLs) and an elevated CA125 level was found upon a PubMed search. A 37-year-old woman presenting with massive ascites, bilateral pleural effusions and a pelvic mass measuring 20 x 18 x 10 cm is described. The pre-operative serum CA125 was 920.4 U/ml. After total abdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…A notable finding in this case however, is that the patient had an elevated CA-125 of 237.5 U/mL. Elevated CA-125 has been described in association with uterine leiomyomas (Dong et al, 2015) as well as sarcomas including leiomyosarcoma, stromal sarcoma and rhabdomyosarcoma (Duk et al, 1994, Yilmaz et al, 2009, Menczer et al, 2014, Holcomb et al, 1999). Authors have postulated that this elevation is due to reactive mesothelial cells, and there have been conflicting reports as to whether CA-125 level predicts extrauterine disease involvement and higher disease stage (Duk et al, 1994, Yilmaz et al, 2009).…”
Section: Discussionmentioning
confidence: 61%
“…A notable finding in this case however, is that the patient had an elevated CA-125 of 237.5 U/mL. Elevated CA-125 has been described in association with uterine leiomyomas (Dong et al, 2015) as well as sarcomas including leiomyosarcoma, stromal sarcoma and rhabdomyosarcoma (Duk et al, 1994, Yilmaz et al, 2009, Menczer et al, 2014, Holcomb et al, 1999). Authors have postulated that this elevation is due to reactive mesothelial cells, and there have been conflicting reports as to whether CA-125 level predicts extrauterine disease involvement and higher disease stage (Duk et al, 1994, Yilmaz et al, 2009).…”
Section: Discussionmentioning
confidence: 61%
“…Uterine leiomyoma is the most common benign gynecological neoplasm [16]. However, elevated CA125 levels, a massive leiomyoma and large ascites, which is collectively known as pseudo-Meigs syndrome, are rarely seen in this condition [11][12][13][14][17][18][19][20]. In addition, no agreement on the pathogenesis of this rare condition has been established.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudo-Meigs syndrome is de ned as a disorder similar to Meigs syndrome, in which neoplasms of a different histological types, including uterine leiomyomas, are present [8][9][10]. Uterine leiomyomas that present as pseudo-Meigs syndrome have already been described in the literature [11][12][13][14]. However, few cases of pseudo-Meigs syndrome in which a leiomyoma is implanted on the omentum have been reported [15].…”
Section: Introductionmentioning
confidence: 99%
“…Du et al, reported a 33.3% rate of cellular leiomyomatosis in their study of intravenous leiomyomatosis [29]. Hemorrhagic cellular leiomyoma was observed in cases of myomectomy performed during a cesarean section.…”
Section: Nomentioning
confidence: 97%